2016
DOI: 10.7314/apjcp.2016.17.3.953
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Associations between TNF-α Polymorphisms and Cervical Cancer in Thai women

Abstract: The risk of developing cervical cancer in women infected with human papillomavirus (HPV) may be influenced by an individual's genetic susceptibility. Published data linking single nucleotide polymorphisms (SNPs) in the tumor necrosis factor-alpha (TNF-α) promoter region at positions -308G>A (rs1800629) and -238G>A (rs361525) to cervical cancer risk have been inconclusive. In this study, we examined 251 cervical specimens and classified them into two groups according to their cytological findings: 121 cancer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The two most commonly studied SNPs are in the promoter region of TNF , two G versus A transitions at positions −238 and −308; these have been shown to influence the expression of TNF-α [28,29]. A large number of studies have investigated the associations of TNF -238 G/A and/or −308G/A variants with cervical cancer risk, but results are contradictory [30,31]. Our data showed that −238 GG/GA and −308 AA genotypes in TNF were associated with increased cervical cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The two most commonly studied SNPs are in the promoter region of TNF , two G versus A transitions at positions −238 and −308; these have been shown to influence the expression of TNF-α [28,29]. A large number of studies have investigated the associations of TNF -238 G/A and/or −308G/A variants with cervical cancer risk, but results are contradictory [30,31]. Our data showed that −238 GG/GA and −308 AA genotypes in TNF were associated with increased cervical cancer risk.…”
Section: Discussionmentioning
confidence: 99%